2022
DOI: 10.3389/fsufs.2022.1032708
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic characterization of phosphate solubilizing microorganisms and their role in improving soil phosphate solubility, yield of upland rice (Oryza sativa L.), and phosphorus fertilizers efficiency

Abstract: Phosphate solubilizing microbes (PSM) can improve soil P availability by P dissolution. These microbes can make substances that regulate plant growth, which promotes plant growth. The present study aimed to characterize PSM and determine how PSM application affected P solubilization, soil phosphatase activity, and upland rice yield. The greenhouse experiment used a factorial randomized block design (RBD) with two factors and three replications. The first factor was PSM isolates, which came in four different fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Furthermore, fertilizers based on microorganisms, such as those used in this study (Claroideoglomus etunicatum, Funneliformis mosseae, Glomus aggregatum, Rhizophagus intraradices, Trichoderma, Streptomyces, Bacillus, and Pseudomonas), can aid in the solubilization of phosphorus in the soil, the second most important nutrient for plants after nitrogen, alongside nitrogen fixation and mineral absorption stimulation, thereby stimulating plant growth and ultimately increasing production. On the other hand, chemical fertilizers are rich in macronutrients N, P, K (40)(41)(42). Therefore, it is important to consider these factors when selecting a fertilizer for a specific crop and environment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fertilizers based on microorganisms, such as those used in this study (Claroideoglomus etunicatum, Funneliformis mosseae, Glomus aggregatum, Rhizophagus intraradices, Trichoderma, Streptomyces, Bacillus, and Pseudomonas), can aid in the solubilization of phosphorus in the soil, the second most important nutrient for plants after nitrogen, alongside nitrogen fixation and mineral absorption stimulation, thereby stimulating plant growth and ultimately increasing production. On the other hand, chemical fertilizers are rich in macronutrients N, P, K (40)(41)(42). Therefore, it is important to consider these factors when selecting a fertilizer for a specific crop and environment.…”
Section: Discussionmentioning
confidence: 99%
“…Fitriatin et al [18] reported that Burkholderia sp. isolate increased soil phosphatase activity by 142.7% compared to the control.…”
Section: Soil Phosphatase Enzymementioning
confidence: 99%
“…As functional microorganisms, Phosphate-Solubilizing Bacteria (PSB) are not only found in soil and environments but also as plant endophytes. Many previous studies investigated the exploration and effect of PSB in varying agricultural practices, such as conventional and organic wetland [10,11], upland rice [12], calcareous soil [13], saline soil [14], and others.…”
Section: Introductionmentioning
confidence: 99%